(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Effective geoconservation systems are crucial to the activities of subcommissions of the International Subcommission on Stratigraphy, such as the Jurassic Subcommission (ISJS). Fundamentally, the core activity of any Subcommission, the establishment of Global Stratotype Sections and Points (GSSPs) is a conservation activity in itself, involving the selection of key sites, to be maintained as references for subsequent consultation. Without adequate national site protection and management systems this fundamental function is liable to fail as the selected site remains vulnerable to loss and damage. In addition, strict conservation systems applied without adequate understanding of the needs of research and education can also prevent or significantly inhibit geological science and the use of sites such as GSSPs. To address these extreme scenarios and assist the development of a more scientific approach to conservation of geological sites of stratigraphical and palaeontological importance during dialogues with administrative authorities, a Statement defining categories of palaeontological heritage requiring protection and the basic requirements needed to achieve the conservation of stratotype localities is here proposed. The context of the protection of Jurassic sites within other international projects is also reviewed, in particular the IUGS Geosites project, within which all GSSPs will be listed.